Biology of Fouling in Neendakara Port, a Tropical estuary in the South West Coast of India - DHARMARAJ, K; NAIR, N BALAKRISHNAN (Fishery Technology, 2017)
Species composition and some aspects of the biology of the fouling community in Neendakara port (southwest coast of India) has been examined for a period of one year. Fouling organisms were collected with a system of glass panels exposed for varying durations and during different months in the port. One species of sponge, nine species of coelenterates, thirteen species of polyzoans, four species of mud-tube dwelling polychaetes, four species of serpulids, one species each of mud-tube forming amphipod and tanaid, two species of oysters, six species of mussels and not less than eight species of tunicates were the macro foulers which settled over the panels. Monthly and seasonal settlement of the different species have been recorded. Fouling has been a continuous process occurring throughout the year in Neendakara port with slightly fluctuatingbiomass and considerably varying species composition. Alternate speciesdominance of marine and brackish water forms has been an important feature of fouling in the area. Number of species of the sedentary fouling animals represented on test panels has been high during the highly saline premonsoon period and low during the monsoon period.